2012
DOI: 10.1186/1479-5876-10-176
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prevalence trends of transfusion transmissible infections among blood donors at four chinese regional blood centers between 2000 and 2010

Abstract: BackgroundIn China, high prevalence of HBV and HCV parallels with the growing epidemic of syphilis and HIV in the general population poses a great threat to blood safety. This study investigated the prevalence of serologic markers for transfusion transmissible infections (TTIs) among four Chinese blood centers.MethodsWe examined whole blood donations collected from January 2000 through December 2010 at four Chinese blood centers. Post-donation testing of TTIs (HIV, HBV, HCV and syphilis) were conducted using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 23 publications
(25 reference statements)
13
47
7
Order By: Relevance
“…A study in the five Chinese blood centers participating in the Retroviral Epidemiological Donor Study II International - China (REDS-II China) found that among the 226,489 whole blood donors, the majority (94%) of them were younger than 45 years, and half (52%) were younger than 25 years [7]. The result is comparable to a study in four large blood centers which found that approximately half (49%) of the donors were 25 years or younger, and only 8% were older than 45 years [3]. A study in a province capital blood center found that among the 381,185 donors who donated whole blood between 2008 and 2012, 61% of them were younger than 25 years [32].…”
Section: Donor Selectionsupporting
confidence: 77%
See 2 more Smart Citations
“…A study in the five Chinese blood centers participating in the Retroviral Epidemiological Donor Study II International - China (REDS-II China) found that among the 226,489 whole blood donors, the majority (94%) of them were younger than 45 years, and half (52%) were younger than 25 years [7]. The result is comparable to a study in four large blood centers which found that approximately half (49%) of the donors were 25 years or younger, and only 8% were older than 45 years [3]. A study in a province capital blood center found that among the 381,185 donors who donated whole blood between 2008 and 2012, 61% of them were younger than 25 years [32].…”
Section: Donor Selectionsupporting
confidence: 77%
“…For example, the blood donation rate in China is still low at 9‰ of the whole population, which is much lower than the WHO-recommended level of 10-30‰ [3]. The required donation interval between whole blood donations is relatively long, and whole blood donation volume per donation is relatively small when compared to other countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable observation of serious concern, was that higher TTI reactivity was observed in repeat donors (1.4 %, n = 32,037) as compared to first time donors (0.63 %, n = 51,828) as depicted in Table 1. This is in sharp contrast to what is usually reported in literature [16][17][18]. However the Retrovirus Epidemiology Donor Study (REDS) reports that incidence rates of TTI are not necessarily lower in whole blood donors who donate regularly and more frequently.…”
Section: Post Referral Follow Upcontrasting
confidence: 55%
“…Likely, comparing the results with another study of Pakistan highlighted the increased prevalence of HBV among blood donors in the present study (Shah et al, 2010). Whereas, the sero prevalence of TTIs among Chinese population revealed less frequencies of HBV and HCV (0.86%, 0.51%) as compared to that of Pakistani population (Li et al, 2012). Higher prevalence of HBV and HCV as compared to other potent infectious agents among blood donors had been accredited to the viral transmission during their window period, chronic and asymptomatic hepatitis C infections, unavailability of vaccinations and inability to detect occult HBV infection (HBV DNA in blood) through routine HBsAg testings (Khattak et al, 2002;Bhattacharya et al, 2007).…”
Section: Journal Of Infection and Molecular Biology April 2015 | Volumentioning
confidence: 70%